Knowledge sharing in the supply chain networks: A perspective of supply chain complexity drivers - Hareer Fatima Ahmed; Amin Hosseinian-Far; Rasoul Khandan; Dilshad Sarwar; Khushboo-E-Fatima (Logistics, 2022)
Background: Knowledge transfer has been an important aspect in supply chain systems; however, there are many factors that affect the impact of transfer effectiveness. In previous studies, less attention has been given to the process of knowledge transfer and therefore, this paper highlights the significance of the process of knowledge transfer in supply chain processes. Enhanced supply chain networks have better performance when knowledge sharing is present, and it is important to identify and eliminate any supply chain complexity to improve the supply chain processes. Methods: A systematic review on the literature has been conducted to critically identify and evaluate the factors of supply chain complexity which impact knowledge transfer. Findings: The findings highlight the key benefits of effective knowledge transfer in supply chain systems by identifying risks associated with supply chain networks. Conclusion: The balanced power of facilitating knowledge transfer in supply chain processes helps in supply chain partnerships and reduces the supply chain complexity. This paper has both theoretical and practical contributions as it adds to the literature by identifying the factors of supply chain complexity drivers which are impacting the knowledge transfer.
Keywords: 650; knowledge transfer; supply chain complexity; supply chain complexity drivers; supply chain systems; systematic review